A Dynamic Control Methodology for DC Fault Ride Through of Modular Multilevel Converter based High Voltage Direct Current Systems. (May 2022) - Inwumoh, Jude; Baguley, Craig; Gunawardane, Kosala
Highlights: A novel energy-based control is proposed for achieving leg and arm energy balance such that the components of the circulating currents responsible for feeding the DC fault with transient DC oscillations are eliminated successfully. The control strategy encourages DC-FRT capability through STATCOM operation using reactive power compensation to support the AC grid voltage. The dynamic response of the control method makes it possible to eliminate the transients that exist at the time of transition between STATCOM mode and the normal mode of operation. The proposed scheme ensures capacitors' transients overvoltage is eliminated through balancing of the equivalent arm capacitor voltage. Abstract: High Voltage Direct Current (HVDC) transmission has provided a variety of possibilities for renewable energy resources and regional substations to boost power supply reliability and operational flexibility. To accommodate this development, the Modular Multilevel Converter (MMC) has been pervasively selected as a potential converter solution for HVDC applications due to its modularity and scalability. However, several technical challenges can hamper their practical applications and deployment, especially in modelling, controlling, and protecting the MMC-HVDC grids, since conventional control schemes struggle to achieve DC fault protection, converter energy balance, and DC Fault Ride Through (DC-FRT) capability. As a result, a novel control structure is proposed to ensure a proper dynamic response, balance arm and leg internal energies, minimise oscillations in DC, and offer DC-FRT capability alongside Static Synchronous Compensation (STATCOM). The result analysis under normal and pole-to-pole DC fault is done in MATLAB/Simulink to validate the proposed control scheme. Graphical abstract: Image, graphical abstract